The importance of the political order for peace. Issue 1 (9th January 2017) - Mikulan Kildi, Janja; Cepoi, Victor
Abstract : Purpose: The purpose of this paper is to address the issue of security challenges in the selected states in Eurasia and Central and Eastern Europe from the perspective of peace and politics. Since the security situation differs significantly across the sub-regions under scrutiny, the main objective of the current research is to establish and test a theoretical model of relevant combinations of political factors and their relation to peace. The theoretical framework has been designed by following Fukuyama's idea of political order and upgraded with the newly constructed index of social exclusion. Design/methodology/approach: According to the objective and methodological gaps in this field, the paper applies comparative fuzzy set analysis. The method relies on the theoretical framework and empirical data and allows a constant communication between the two. It has allowed the research to focus on what conditions are necessary and/or sufficient for peace in the selected countries. Findings: It is evident there are several different paths to achieve peace. However, the rule of law clearly constitutes both the necessary and sufficient conditions for peace in the selected regions. Moreover, the results of the research reveal that the concepts of interest are highly interlinked with each other, especially when it comes to the rule of law, state, and democratic accountability. Thus, further research should focus on in-depth analysis of each particular case to explore which conditions or combinations are decisive in particular setting. Originality/value: Such findings can contribute to improving the areas where Eurasian countries are still lagging behind. Further research should focus on small but significant differences within these four groupings of countries, to improve the understanding of prerequisites for peace and contribute to the development of state and human security in the EU neighborhood.